2015
DOI: 10.3855/jidc.6122
|View full text |Cite
|
Sign up to set email alerts
|

Genetic determinants of pathogenicity of Escherichia coli isolated from children with acute diarrhea in Maputo, Mozambique

Abstract: Introduction: Diarrheagenic Escherichia coli (DEC) represents one of the leading cause of diarrhoea in developing countries. In this study a molecular approach was applied for the detection of diarrheagenic Escherichia coli (DEC) circulating in Maputo, Mozambique. Methodology: All isolates were PCR tested for species-specific genes and for 11 molecular markers: stx1, stx2, eae, bfpA, lt, st, ipaH, aap, aggR CVD432 and daaE. Results: Of the 80 E. coli isolated, 74% were potential DEC: 21% EIEC, 19% EPEC, 15% EA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 13 publications
(30 reference statements)
1
8
3
Order By: Relevance
“…In contrast with our findings, recent studies conducted in sub-Saharan Africa associated EIEC to diarrhea [35,36]. At least, the lower circulation of EHEC is not surprisingly, since previous studies conducted in Mozambique revealed low circulation of this pathotype in Manhiça [5] and absence in Maputo city [11,14,15]. Nevertheless, the circulation of EHEC have been reported from a number of other locations in Africa, including Nigeria [37], and Uganda [38].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast with our findings, recent studies conducted in sub-Saharan Africa associated EIEC to diarrhea [35,36]. At least, the lower circulation of EHEC is not surprisingly, since previous studies conducted in Mozambique revealed low circulation of this pathotype in Manhiça [5] and absence in Maputo city [11,14,15]. Nevertheless, the circulation of EHEC have been reported from a number of other locations in Africa, including Nigeria [37], and Uganda [38].…”
Section: Discussioncontrasting
confidence: 99%
“…Previous reports on DEC prevalence in Maputo city (80 km from Manhiça) described a variable circulation of EIEC (0.3-21%) in children with diarrhea [11,14,15], although not associated with the disease, whereas the detection of DAEC by phenotypic assay was significantly associated with diarrhea (22.8% in cases vs. 11% in controls, p < 0.0001) [11]. It is unknow which factors are implicated in the variation of epidemiology of EIEC and DAEC between Manhiça (rural setting) and Maputo (urban setting).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Atypical EPEC have been recovered from children's diarrhea in countries and population groups of middle to high socioeconomic level [ 34 , 35 ]. Typical EPEC strains are still prevalent in poor regions of sub-Saharan Africa [ 36 ], but in other developing areas, aEPEC predominates as seen in developed countries [ 37 ]. In America, tEPEC (as defined through classic serogroup determination) was prevalent some decades ago, mainly in developing regions [ 13 , 15 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In developing countries, it has also been recognised as an agent of infantile diarrhoea, and it can also be found in non-diarrhoea samples [65,66]. In South Africa, a prevalence of 20% was reported in children with diarrhoea [61], while a prevalence of 19% has been reported in Mozambique [67]. In this study, it was observed that the eaeA gene was expressed more from samples of children without fever and vomiting, agreeing with previous a study in Denmark where 44% of infected children did not show any sign or symptom of diarrhoea [68].…”
Section: Prevalence Of Dec Pathotypesmentioning
confidence: 99%